2011
DOI: 10.1002/jnr.22808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic administration of estradiol, progesterone, and tibolone on the expression and phosphorylation of glycogen synthase kinase‐3β and the microtubule‐associated protein tau in the hippocampus and cerebellum of female rat

Abstract: Gonadal hormones regulate expression and activation of protein tau. Tibolone is a drug used as first- choice comprehensive treatment for the relief of menopausal symptoms, because it and its various metabolites have estrogenic properties and progestogenic/androgenic effects; however, the effect on the activation of tau protein and its signaling cascade in the brain is unknown. We studied the effect of chronic administration of estradiol (E2), progesterone (P4), and tibolone (TIB) on the expression and phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 78 publications
0
14
0
1
Order By: Relevance
“…Tibolone exerts neuroprotective and antioxidative actions in neurons (Belenichev et al, 2012;de Aguiar et al, 2008;Farfán-García et al, 2014;Pinto-Almazan et al, 2012). Besides, tibolone has shown to exert protective actions against glucose deprivation in a human astrocyte cell model, the T98G cells (Avila Rodriguez et al, 2014).…”
Section: Selective Estrogen Receptor Modulators (Serms) and Selectivementioning
confidence: 95%
“…Tibolone exerts neuroprotective and antioxidative actions in neurons (Belenichev et al, 2012;de Aguiar et al, 2008;Farfán-García et al, 2014;Pinto-Almazan et al, 2012). Besides, tibolone has shown to exert protective actions against glucose deprivation in a human astrocyte cell model, the T98G cells (Avila Rodriguez et al, 2014).…”
Section: Selective Estrogen Receptor Modulators (Serms) and Selectivementioning
confidence: 95%
“…Finally, when ovariectomized female rats were chronically treated with estrogen, progesterone, and tibolone (TIB) (a widely prescribed synthetic steroid with estrogenic, progestogenic, and androgenic actions), less p-Tau in the epitope PHF-1 and more dephosphorylation in the antibody Tau-1 was detected, in both the hippocampus and the cerebellum ( 58 ). In this particular study, no changes were detected in GSK3β Ser 9 in the hippocampus, in contrast to the findings in the cerebellum, suggesting the involvement of different pathways or a region-specific action for this enzyme.…”
Section: Hormone Actions and Their Relation To Neurodegenerative Disementioning
confidence: 99%
“…Furthermore, tibolone decreases the activity of acetylcholinesterase and choline acetyltransferase in the medial septum/diagonal band of Broca of ovariectomized monkeys [34], suggesting a modulation of cholinergic neurons. It has also been shown that tibolone decreases the hyperphosphorylation of the neuronal protein Tau in the hippocampus and cerebellum [35]. In addition, tibolone reduces anxiety, at least in young female rats [36].…”
Section: Introductionmentioning
confidence: 97%